Ya-Yas in bloom : a novel - Wells, Rebecca (New York : HarperCollins Publishers, 2005)
YA-YAS IN BLOOM reveals the roots of the Ya-Yas' friendship in the 1930s and roars with all the raw power of Vivi Abbott Walker's 1962 T-Bird through sixty years of marriage, child-raising, and hair-raising family secrets.
Keywords: Grandparent and child -- Fiction; Domestic fiction